Role of Semen on Vaginal HIV-1 Transmission and Maraviroc Protection - Council, Olivia D. (Antimicrob Agents Chemother, 2015)
We used bone marrow/liver/thymus (BLT) humanized mice to establish the effect of semen on vaginal HIV infection and on the efficacy of topically applied maraviroc. Our results demonstrate that vaginal transmission of cell-free HIV occurs efficiently in the presence of semen and that topically applied maraviroc efficiently prevents HIV transmission in the presence of semen. We also show that semen has no significant effect on the transmission of transmitted/founder viruses or cell-associated viruses.